2015
DOI: 10.1016/j.actamat.2015.01.030
|View full text |Cite
|
Sign up to set email alerts
|

A discrete dislocation plasticity study of the micro-cantilever size effect

Abstract: Micro-cantilevers are increasingly used to extract elastic and plastic material properties through controlled bending using a nanoindenter. Focused Ion Beam milling can be used to produce small scale single crystal cantilevers with cross-sectional dimensions on the order of microns, and electron backscatter diffraction (EBSD) allows cantilevers to be milled from a grain with a desired crystal orientation. Micro-cantilever bending experiments suggest that sufficiently smaller cantilevers are stronger, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 45 publications
(69 reference statements)
5
47
0
Order By: Relevance
“…Moreover, the bending stress in the plastic regime is size dependent with the smaller specimens exhibiting a larger bending stress. This is consistent with a wide body of both experimental [27,28] and computational [11,30,31] gations that suggest that the bending stress is size dependent in the micron size regime. We shall explore the origins of this size effect in more details in Sect.…”
Section: Cantilever Beam Bendingsupporting
confidence: 76%
See 2 more Smart Citations
“…Moreover, the bending stress in the plastic regime is size dependent with the smaller specimens exhibiting a larger bending stress. This is consistent with a wide body of both experimental [27,28] and computational [11,30,31] gations that suggest that the bending stress is size dependent in the micron size regime. We shall explore the origins of this size effect in more details in Sect.…”
Section: Cantilever Beam Bendingsupporting
confidence: 76%
“…Moreover, in this setting the imposed loads also generate shear stresses. In their study, Tarleton et al [31] performed small strain DDP Fig. 2 Sketch of the boundary value problem of the tip loading of the cantilever beam.…”
Section: Comparison Of Finite Strain and Small Strain Ddp Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pa ⋅ s is the assumed edge drag coefficient in zirconium. Further details on DDP as applied to the mechanical behavior of small-scale zirconium can be found in the work of Tarleton et al [9]. Although the hydridematrix interface could impede dislocation motion in reality, this interaction is not included here for simplicity; the hydride dipole and matrix dislocations are only allowed to interact via their stress fields.…”
Section: Theorymentioning
confidence: 99%
“…For instance, Shishvan [15] showed the simpler two-dimensional DDD studies are more successful in a range of applications encompassing microstructure evolution and plastic mechanism. Tarleton [16] adopted a planar discrete dislocation dynamic model to simulate micro-cantilever bending for hcp crystals oriented for plane strain prismatic slip. The results showed that pure bending interpretations of the micro-cantilever size effect do not reveal its full behavior and the inhomogeneous, highly localized stress influence the strengthening mechanisms and mechanical property.…”
Section: Introductionmentioning
confidence: 99%